Neuronal nitric oxide synthase regulates regional brain perfusion in healthy humans. Issue 5 (30th April 2021) - O'Gallagher, Kevin; Puledda, Francesca; O'Daly, Owen; Ryan, Matthew; Dancy, Luke; Chowienczyk, Philip J; Zelaya, Fernando; Goadsby, Peter J; Shah, Ajay M
Abstract: Aims: Neuronal nitric oxide synthase (nNOS) is highly expressed within the cardiovascular and nervous systems. Studies in genetically modified mice suggest roles in brain blood flow regulation while dysfunctional nNOS signalling is implicated in cerebrovascular ischaemia and migraine. Previous human studies have investigated the effects of non-selective NOS inhibition but there has been no direct investigation of the role of nNOS in human cerebrovascular regulation. We hypothesized that inhibition of the tonic effects of nNOS would result in global or localized changes in cerebral blood flow (CBF), as well as changes in functional brain connectivity. Methods and results: We investigated the acute effects of a selective nNOS inhibitor, S-methyl-L-thiocitrulline (SMTC), on CBF and brain functional connectivity in healthy human volunteers ( n = 19). We performed a randomized, placebo-controlled, crossover study with either intravenous SMTC or placebo, using magnetic resonance imaging protocols with arterial spin labelling and functional resting state neuroimaging. SMTC infusion induced an ∼4% decrease in resting global CBF [−2.3 (−0.3, −4.2) mL/100g/min, mean (95% confidence interval, CI), P = 0.02]. In a whole-brain voxel-wise factorial-design comparison of CBF maps, we identified a localized decrease in regional blood flow in the right hippocampus and parahippocampal gyrus following SMTC vs. placebo (2921 voxels; T = 7.0; x = 36; y = −32; z = −12; P < 0.001). This was accompanied by a decrease in functional connectivity to the left superior parietal lobule vs. placebo (484 voxels; T = 5.02; x = −14; y = −56; z = 74; P = 0.009). These analyses adjusted for the modest changes in mean arterial blood pressure induced by SMTC as compared to placebo [+8.7 mmHg (+1.8, +15.6), mean (95% CI), P = 0.009]. Conclusions: These data suggest a fundamental physiological role of nNOS in regulating regional CBF and functional connectivity in the human hippocampus. Our findings have relevance to the role of nNOS in the regulation of cerebral perfusion in health and disease.